Canon law in the age of reforms (ca. 1000 to ca. 1150) - Rolker, Christof 1979-; Somerville, Robert 1940- (Washington The Catholic University of America, 2023)
"This monograph addresses the history of canon law in Western Europe between ca. 1000 and ca. 1150, specifically the collections compiled and the councils held in that time. The main part consists of an analysis of all major collections, taking into account their formal and material sources, the social and political context of their origin, the manuscript transmission, and their reception more generally"--
Canon law and canonical collections : an introduction -- Burchard of worms : Canon law in a 'Europe of bishops' A 'Europe of Bishops' -- Monastic Canon law -- The 'Gregorian' collections -- The schools of Northern France and beyond -- Papal councils, 1049-1179 : selected topics (by Robert Somerville).
Includes bibliographical references and index
Keywords: Canon Law -- History; Law reform -- History